The Divine Feminine as a Healing Mechanism to Trauma Case Study: The Protagonist of The Secret Life of Bees - BEKKAYE ,Amina; TOUHAMI ,Ibtissam (Faculty of Letters and Foreign Languages Department of English, 2018)
This dissertation delves into a Southern American novel, projecting trauma theory as a basis for psychological analysis, with regard to the protagonist in Sue Monk Kidd’s The Secret Life of Bees (2002), and then traces her healing process, which will reveal the existence of common features that correlate aspects of the Divine Feminine with Cathy Caruth’s memory narratives of healing. The latter is humbly achieved through an introduction, a theoretical framework, and two chapters; the theoretical framework is composed of two sections; the first is an exploration to Caruth’s theory of trauma, where it will be followed chronologically whereas the second will function as both an introduction to the divine feminine with its aspects, mainly the ‘Moon Cycle’ three Goddesses, while the second chapter will label the protagonist as a trauma victim; besides, it will situate The Bees (2002) as Goddess text, mainly under the embedded features and symbolisms in it. Moreover, the characters of the Calendar Sisters will be compared to the Triple Goddess archetypes, and the matching similarities will likely nominate them to be therapists to the protagonist. So, this will smoothly pave the way to the third and analytical chapter, wherein, the influence of the Calendar Sisters, the black Madonna, and the Daughters of Mary on Lily’s healing will be discussed. With this intention, this paper aims to examine whether or not the aspects of the divine feminine, particularly those related to the Triple Goddess or the ‘Moon Cycle’, are effective in healing Lily’s trauma, especially, once applied by the Calendar sisters. By the end, the paper will highlight the reliability of using the divine feminine as a healing mechanism to treat trauma